Digital Marketing Communication Model of Healthy Eat Lifestyle among Vegan on Indonesia - Daniel Susilo; Juan Carlos M. Smith (CV. Media Digital Publikasi Indonesia, 2023)
This paper would to challenge the Model of Digital Marketing Communication and promotion of Healthy Lifetyle among Vegan in Indonesia. Sustainable product and healthy product are important part of our life since we need it in order to achieve good life and good health. This paper With the power of social media and internet, we create our own space to talk about things relathed to healthy life and healthy product. This paper use Content Analysis as methodologu. However by content analysis, one or two brand sometimes didn’t go for the standard value and as a result, it is like how Baudrillard said about hyperreality, that a big name and digital content could overwrite our perception on things. As a result we cannot differ the true quality or just influenced by name only for promotion of Healthy lifetyle.